Zn@C Core–Shell Nanocomposite for Rechargeable Aqueous Zn//MnO2 Batteries with Long Lifetime. Issue 4 (4th April 2019) - Wei, Hang; Hu, Xiao; Zhang, Xianfeng; Yu, Zhifeng; Zhou, Tianyi; Liu, Yang; Liu, Yongguang; Wang, Yue; Xie, Jiexin; Sun, Lianfeng; Liang, Minghui; Jiang, Peng
Abstract : Rechargeable zinc‐based aqueous batteries are a promising candidate for next‐generation energy storage devices because of the high theoretical energy density of Zn as well as the availability, safety, and cheap price of Zn‐based aqueous batteries. A Zn@C core–shell composite is designed to overcome two problems of Zn anodes, that is, the formation of Zn dendrites and the corrosion/loss of Zn anode during the charge–discharge process, influencing the lifetime of Zn‐based aqueous batteries. The prepared Zn@C composite from ZnO@C with electrochemical reduction is robust as the anode for a Zn@C//MnO2 battery, and a 98.8% retention after 400 cycles is obtained at a discharge rate of 5 C. The specific capacitance of Zn@C//MnO2 battery can reach 135 mAh gZn −1 at 3 C, and the energy density of this battery can reach 75.9 Wh Kg −1 . The coated carbon layer on Zn/ZnO plays a role in protecting Zn/ZnO from leaching or corrosion by KOH, so the structure of Zn@C is a key factor in improving the cycling lifetime of Zn‐based aqueous batteries. Abstract : Carbon‐coated Zn metal (Zn@C) anode serves as the robust electrode for a Zn‐MnO2 alkaline battery with long lifetime and little capacitance fading. The structure of the Zn@C core–shell composite plays an important role in the high performance of the Zn@C//MnO2 battery.